2021
DOI: 10.1039/d1ee00166c
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the respective effects of heteroatom-doped carbon materials in batteries, supercapacitors and the ORR to design high performance materials

Abstract: Heteroatom-doped carbon materials (HDCMs) have been widely studied as one of the most prominent material candidates for a wide range of applications, such as batteries, supercapacitors (SCs) and ORR. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
269
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 434 publications
(270 citation statements)
references
References 423 publications
1
269
0
Order By: Relevance
“…56 (3) The pyridinic/ pyrrolic N species and some oxygen-containing groups are electrochemical active sites for providing pseudocapacitance (as shown in Figure S14). 57 It is agreeable that the N and O contents are still abundant even under CO 2 activation for a long time, suggesting our promising fabrication strategy. Moreover, it is not hard to imagine that extra other heteroatoms doping (such as S, B, and P) and nanoscale electrocatalyst loading in N-PCM-9 can be achieved through precursors regulation, providing a composition controllable preparation route.…”
Section: The Microstructure and Composition Of N-pcm-xmentioning
confidence: 61%
“…56 (3) The pyridinic/ pyrrolic N species and some oxygen-containing groups are electrochemical active sites for providing pseudocapacitance (as shown in Figure S14). 57 It is agreeable that the N and O contents are still abundant even under CO 2 activation for a long time, suggesting our promising fabrication strategy. Moreover, it is not hard to imagine that extra other heteroatoms doping (such as S, B, and P) and nanoscale electrocatalyst loading in N-PCM-9 can be achieved through precursors regulation, providing a composition controllable preparation route.…”
Section: The Microstructure and Composition Of N-pcm-xmentioning
confidence: 61%
“…These data indicate that the mass specific capacitance is roughly 377 F/g. This value is higher than the specific capacitance of several high performance electrode materials [44,45] as shown in Table 4. Comparison of the gravimetric capacitances listed in Table 3 leads us to the conclusion that practically only doped graphene and B containing carbons display a higher value than our biomassbased CA carbon.…”
Section: Electrocatalytic Applicationmentioning
confidence: 68%
“…al. [149] summed up heteroatom-doped carbon materials as some of the most significant candidates for usage in various applications, including oxygen reduction reactions, SCs, and batteries. They concluded that the doping content and position of the doping affect the material's performance in electrocatalysis and energy storage conversion.…”
Section: Mechanisms Of High-performance S-doped Carbon-based Scsmentioning
confidence: 99%